Designing of the Quest-Tour Itinerary "Early 19th Century. German Cultural Heritage in Kharkiv" - Chaika, Tatiana (My University, 2023)
Purpose. The continuous evolutionary change in consumer preferences encourages the travel business to continuously look for new innovative forms and techniques to meet consumer demand. There is a growing demand in the travel, tourism and hospitality sector for unique, personalized and sustainable travel. In this regard, the search for creative solutions to create highly competitive travel and sightseeing products that take into account current trends in consumer preferences is relevant. One possible avenue in this context is the creation of cultural heritage tourism products. The purpose of this study is to improve approaches to the design of cultural heritage quest-tour itineraries and to test the recommendations developed. Results. Creative tourism plays an important role in developing and maintaining interest in cultural heritage. The creation of travel and sightseeing products based on a combination of the concepts of heritage tourism and creative tourism allows meeting the consumer demand for uniqueness, authenticity, personalization, creative involvement and self-development. It is this combination of modern, innovative types of travel and sightseeing that we consider most promising in terms of providing highly competitive, unique products. Quest-tour is a type of travel and sightseeing service, which can be successfully used in the creation of heritage tourism products in the context of modern trends of changing consumer preferences. Itinerary design techniques for heritage quest-tour should take into account the significance of the excursion sites in terms of presenting the atmosphere of the era in question; the degree of preservation of authentic excursion sites; and the amount of available factual material. In this study, we tested the technique of designing the quest-tour itinerary on the example of our developed quest-tour «Early 19th century. German cultural heritage in Kharkiv». According to the storyline, the quest-tour is about almost the earliest documented period of ethnic German life in Kharkiv. Scientific novelty. The scientific novelty of the study lies in the improvement of the designing technique for quest-tours of cultural heritage on the basis of overlapping the concepts of heritage tourism and creative tourism. Practical value. The practical value of the study lies in the practical validation of the improved technique of designing heritage quest-tours, as well as the possibility of using the results in the practical activities of travel firms in the design of excursion products.

Мета. Постійна еволюційна зміна споживчих уподобань спонукає туристичний бізнес так само безперервно шукати нові інноваційні форми та методи задоволення споживчого попиту. Наразі в секторі туризму та гостинності зростає запит на унікальні, індивідуальні та стійкі подорожі. У зв'язку з цим, актуальним є пошук креативних рішень, які дають змогу створювати висококонкурентоспроможні туристичні та екскурсійні продукти, що враховують сучасні тенденції споживчих уподобань. Одним із можливих напрямів у цьому контексті є створення туристичних продуктів культурної спадщини. Метою цього дослідження є вдосконалення підходів до методичного забезпечення складання маршрутів квест-екскурсій культурної спадщини, а також апробація розроблених рекомендацій. Результати. Креативний туризм відіграє важливу роль у розвитку та підтримці інтересу до культурної спадщини. Створення туристичних та екскурсійних продуктів на основі поєднання концепцій туризму спадщини та креативного туризму дає змогу задовольнити споживчий запит на унікальність, автентичність, персоналізацію, творчу залученість і саморозвиток. Саме таке поєднання сучасних інноваційних видів туризму ми вважаємо найперспективнішим з точки зору надання висококонкурентоспроможних унікальних туристичних продуктів. Квест-екскурсія є видом екскурсійного обслуговування, який можна вдало використовувати при створенні продуктів туризму спадщини в контексті врахування сучасних тенденцій зміни споживчих вподобань. Методика розроблення маршруту квест-екскурсії туризму спадщини має враховувати значущість екскурсійних об'єктів з точки зору презентації атмосфери епохи, ступеню збереженості автентичних екскурсійних об'єктів, обсягу наявного фактологічного матеріалу. У цьому дослідженні ми апробували методику складання маршруту квест-екскурсії на прикладі розробленої нами квест-екскурсії «Початок 19 століття. Німецька культурна спадщина в Харкові». За сюжетом, квест-екскурсія розповідає чи не про найбільш ранній задокументований період життя етнічних німців у Харкові. Наукова новизна. Наукова новизна дослідження полягає в уточненні методики створення квест-екскурсій культурної спадщини на основі поєднання концепцій туризму спадщини та креативного туризму. Практична цінність. Практична цінність дослідження полягає у практичній апробації вдосконаленої методики розроблення маршруту квест-екскурсій культурної спадщини, а також у можливості використання отриманих результатів у практичній діяльності туристично-екскурсійних фірм під час проектування екскурсійних продуктів.
Розробка маршруту квест-екскурсії "Початок 19 ст. Німецька культурна спадщина у Харкові"
Keywords: German cultural heritage; German minority in Kharkiv; heritage tourism; creative tourism; special interest tourism; quest-tour; tour itinerary; innovations in tourism; німецька культурна спадщина; харківська німецька етнічна спільнота; туризм культурної спадщини; креативний туризм; спеціалізований туризм; квест-екскурсія; екскурсійний маршрут